Intra-household time allocation: gender differences in caring for children - Inmaculada Garcia; José Alberto Molina; Víctor M. Montuenga (Institute for the Study of Labor (IZA), 2009)
This paper analyses the intra-household allocation of time to show gender differences in childcare. In the framework of a general efficiency approach, hours spent on childcare by each parent are regressed against individual and household characteristics, for five samples (Denmark, France, Germany, Italy and Spain), with data being drawn from the European Community Household Panel-ECHP (1994-2001). Empirical results show a clear inequality in childcare between fathers and mothers, with this being more evident in Mediterranean countries. Panel data estimates reveal that, in general, caring tasks are mainly influenced by the presence of young children in the household, by the total non-labor income, and by the ratio of mothers' non-labor income to family's non-labor income, with this latter variable exhibiting a different behavior across genders and across countries.
urn:nbn:de:101:1-20090612126
Keywords: D13; J22; C33; 330; Childcare; gender differences; intra-household; Kinderbetreuung; Familienökonomik; Geschlecht; Zeitbudgetforschung; Dänemark; Frankreich; Deutschland; Italien; Spanien